Predictors of Hospital Stay After Acute Ischemic Stroke in Hospitalized Patients: Retrospective-Cohort Study - Zenaw Debasu Addisu; Teshale Ayele Mega (Cardiology Research and Practice)
Conclusion: In this study, the presence of AF and stroke-related complications, such as aspirational pneumonia, were found to be significant predictors of LOS. Therefore, implementing efficient prevention strategies targeting potentially modifiable risk factors is essential to mitigate the impact of these factors.